PECULIARITIES OF JOURNAL GRAPHICS OF P. KOVZHUN AND E. KOZAK IN LVIV POPULAR SATIRICAL EDITIONS OF 20–30S YEARS OF XX CENTURY - Михалевич, В. В. (Art and Design, 2021)
Purpose. Investigate the national component and stylistic features of satirical graphics of P. Kovzhun and E. Kozak in popular Lviv humorous magazines of the interwar period. Methodology. The applied art analysis makes it possible to investigate, identify, compare and describe the features of satirical graphics and artistic design of Lviv humorous publications of the interwar period. Comparative and historical methods help to trace the work of leading artists in Lviv satirical periodicals of 20–30s years of XX century. Results.Stylistic features of satirical graphics by P. Kovzhun and E. Kozak in Lviv humorous magazines of 20–30s years of the XX century are determined. It is noted that the artistic style of these artists was influenced by Western European art trends, such as: modernism, expressionism, cubism, futurism. In their graphics, cartoonists use similar tools to achieve a greater effect – grotesque, allegory, zoomorphism. It is traced that each of these artists had his own individual style of satirical illustration, which was supported by national motives. The article draws parallels between German and Lviv satirical magazine graphics on the example of the magazine "Simplicissimus". It was found out that P. Kovzhun and E. Kozak, as leading artists of humorous publications, in addition to highly artistic illustrations, made high-quality graphic design for the magazines «Maski», «Zyz», «Komar». The artistic design of the covers and technical features of these publications are analyzed. Most satirical magazines had a symmetrical hierarchical composition of the title page with a limited polychrome palette. The logo-name on the cover of the magazine was harmoniously perceived together with the title illustration. The cover was made in color, usually in two colors, magazine covers were monochrome. The semantic load of visual satirical material in humorous editions of the interwar period is established. Scientific novelty. The satirical graphics with an emphasis on the national component of the leading illustrators P. Kovzhun and E. Kozak in Lviv humorous magazines of 20–30s years of the XX century is investigated and compared. The peculiarities of the design of the covers of popular Lviv satirical editions of the interwar twentieth century, such as «Maski», «Zyz», «Komar» are determined. Practical significance. Given data on satirical graphics in Lviv magazines of the 20–30s of the XX century and their artistic design will help in understanding the traditions of Ukrainian Galician satirical illustration and magazine design.